Nursing care for a patient after mastectomy in the home environment – nursing and psychosocial aspects - Ciechacka, Maria (Quality in Sport, 2025)
Cancer is a disease of genetic material and develops as a result of the accumulation of gradually occurring genetic damage. The transformation of a normal cell into a cancer cell, known as neoplastic transformation, requires several gene mutations. In most cancers, DNA defects appear in the cells of individuals genetically predisposed to cancer development, under the influence of environmental factors that damage DNA, known as carcinogens. A significant area of activity is health education, including consultations and counselling for women and their families on health-related matters. Nursing counselling for individuals affected by cancer requires particular knowledge and skills. Therefore, both in the theory and practice of family nursing, there is growing interest in the importance of small groups in the personal development of each individual.